Omega-3 fatty acids: mechanisms underlying “protective effects” in atherosclerosis - Chang, Chuchun L. (2013)
PURPOSE OF REVIEW: This article provides an updated review on mechanistic and molecular studies relating to the effects of n-3 fatty acids (FA) on inhibiting atherogenesis. RECENT FINDINGS: The effects of n-3 FA on modulating arterial lipoprotein lipase (LpL) levels link to changes in lipid deposition in the arterial wall. LpL expression in the arterial wall also relates to local macrophage-mediated inflammatory processes. Increasing evidence suggests that n-3 FA ameliorate inflammation, another key component in the development of atherosclerosis, including decreases in pro-inflammatory cytokine production. n-3 FA inhibit atherogenic signaling pathways and modulate the phenotypes of inflammatory leukocytes and their recruitment in the arterial wall. SUMMARY: New mechanistic insights into the anti-atherogenic action of n-3 FA have emerged. These studies may contribute to future therapeutic advances in preventing mortality and morbidity associated with atherosclerosis.